2015
DOI: 10.1016/j.jccw.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights on Understanding of Keloid Scar: Article Review

Abstract: Keloid scar, dermal benign fibro-proliferative growth that extends outside the original wound and invades adjacent dermal tissue due to extensive production of extracellular matrix, especially collagen, which caused by over expression of cytokines and growth factors. Although many attempts were made to understand the exact pathophysiology and the molecular abnormalities, the pathogenesis of keloid scar is yet to be determined. Even though there are several treatment options for keloid scars include combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
128
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 44 publications
1
128
1
9
Order By: Relevance
“…Insulin-like growth factor-I-inhibition results in decreased and normalized keloid-fibroblast activity in vitro. [1] In a recent microarray study on long non-coding RNAs, an increased expression of the following genes was found in keloid-fibroblasts: FNDC1, CILP2, THBS4, NPTX2, COL5A1, GRIN2D, and CTHRC1. Other genes were downregulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor-I-inhibition results in decreased and normalized keloid-fibroblast activity in vitro. [1] In a recent microarray study on long non-coding RNAs, an increased expression of the following genes was found in keloid-fibroblasts: FNDC1, CILP2, THBS4, NPTX2, COL5A1, GRIN2D, and CTHRC1. Other genes were downregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Earlobes are one of the most common anatomical sites for acquired keloids. [1] Pathologically, fibroblasts from keloids show peculiarities. They are metabolically hyperactive and show an increased migratory activity in cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…frequently occur on the anterior portion of the chest, shoulders, upper back, arms, cheeks and earlobes [1,2,[5][6][7][8][9][10]. Histopathologically, keloids are defined as inflammatory disorders characterized by exhibiting a thickened dermis containing numerous fibroblasts, abnormal vascularization, increased inflammatory immune cells, abundant hyalinised collagen bundles (keloidal collagen) and extracellular matrix (ECM) components including collagen, elastin, fibronectin and proteoglycans such as syndecan and versican, mainly produced by activated fibroblasts [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…Histopathologically, keloids are defined as inflammatory disorders characterized by exhibiting a thickened dermis containing numerous fibroblasts, abnormal vascularization, increased inflammatory immune cells, abundant hyalinised collagen bundles (keloidal collagen) and extracellular matrix (ECM) components including collagen, elastin, fibronectin and proteoglycans such as syndecan and versican, mainly produced by activated fibroblasts [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These histological alterations proper of the keloid tissue have been associated with the elevated production of growth factors such as TGF-β, FGF-2, PDGF, EGF, IGF and VEGF which regulate fibroblast proliferation, ECM synthesis and angiogenesis, and pro-inflammatory cytokines including IL-1α, IL-1β, IL-6 and TNFα which promote fibroblast activation and consequently an excessive deposition of ECM components [1,2,[5][6][7]9,10,15,16]. This is why most studies on keloids focus on dermis and few on epidermis [4,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation